Structure of infaunal communities in New Zealand submarine canyons is linked to origins of sediment organic matter - Daniel Leduc; Scott D. Nodder; Ashley A. Rowden; Max Gibbs; Katrin Berkenbusch; Anna Wood; Fabio De Leo; Craig Smith; Julie Brown; Sarah J. Bury; Arne Pallentin (Limnology and Oceanography, 2020)
Submarine canyons can facilitate the transfer of land‐derived organic matter to the deep sea. Here, we investigated links between variability in organic matter availability from land and marine sources and infauna communities in two contrasting canyon systems off New Zealand and used stable isotope analyses to identify potential food sources of benthic invertebrates. Kaikōura Canyon, a steep, short canyon close to the shore, was characterized by high food availability and varying proportions of marine‐ and land‐derived organic matter, whereas Hokitika Canyon, a narrow and lower‐gradient canyon that extends further from the coast, was characterized by low food availability and mostly land‐derived sediment organic matter throughout. Both macrofaunal and meiofaunal abundance and biomass were greater in Kaikōura Canyon than in Hokitika Canyon. Correlation analyses suggested that land‐derived organic matter may contribute to increased meiofaunal abundance in Kaikōura Canyon. Carbon and nitrogen isotopic analyses, however, did not provide unequivocal support for the uptake of land‐derived material by large benthic invertebrates in Kaikōura Canyon. Infaunal abundance and biomass were low throughout Hokitika Canyon despite similar concentrations of land‐derived organic matter in sediments of both canyons, which suggests that variations in marine‐derived organic matter inputs is the main driver of community differences among canyons. Refractory vascular plant material by itself may not provide an adequate food supply to infaunal organisms, but may represent a complementary food resource when more labile marine phytodetritus is also readily available.